Autonomous Mobile Device Controlled by On-chip Network of Intelligent Sensors for Indoor Environment Navigation - Tanase, Cr. A.; Graur, A.; Gaitan, V. G.; Popa, V. (Elektronika ir Elektrotechnika, 2009)
The aim is to present the carrying out of an on-chip system (SoC) round about of an on-chip network (NoC) implemented on a FGPA structure. The hardware system is developed in order to control a mobile autonomous device that is able to search and track a mobile target, detecting and avoiding all obstacles in its route. The device consists mainly of two components: 1) Sensorial (Intelligent sensors) for searching the target and for detection of the obstacles, made up of a great number of sensors of different kinds; 2) Informatics to determine the target, establishing the route to go on, for analysis and control of the information taken over from the sensors. It is entirely implemented on a reprogrammable FPGA device. The developed system on-chip (SoC) is a network of functional units (NoC) that has to receive raw data from the sensors and to transform it in as much useful information as possible. Ill. 7, bibl. 7 (in English; summaries in English, Russian and Lithuanian).